Uganda: Policies for Improved Soil Nutrient Management, Output Marketing Survey, 1999-2000 - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
This survey was conducted to analyze the market-land degradation linkages by focusing on output traders in Uganda. The data presented originates from the first round of the survey, conducted in 1999-2000. A total of 544 output traders - dealing in coffee, maize, cotton, and cassava were sampled for interview. Depending on their operational size and location, sample traders were divided into four categories: (i) exporters, (ii) Kampala traders, (iii) main town traders, (iv) small trader in primary market with a fixed premise, and (v) itinerant traders. The exporters are the largest traders, largely based in the nation's capital, and well-endowed with capital. The number of respondents for each district was determined depending on the contribution of the district to the national production of the commodity considered. The Output Marketing Survey is part of a larger project "Policies for Improved Soil Nutrient Management in Uganda" which attempts to assess the impact of different causal factors and identify effective policy strategies to combat soil nutrient depletion problem in the highlands of Uganda. The research has utilized market, community, and household surveys to measure the impact of past and present policies on soil nutrient management in the Ugandan highlands; and developed market and household level models based on the surveys to evaluate the impact of alternative policy options. A related survey conducted under the same larger project is Uganda: Policies for Improved Land Management Dataset, 1999-2001 which offers data on community concerns and priorities, establishment and change of local council boundaries, population change, use of local council revenue, infrastructure and services, programs and organizations, land rights, and collective resource management from 107 communities across Uganda.